Directly embedded Ni3S2/Co9S8@S-doped carbon nanofiber networks as a free-standing anode for lithium-ion batteries. Issue 1 (13th November 2020) - He, Zizhou; Guo, Hui; LaCoste, Jed D.; Cook, Ryan A.; Hussey, Blake; Zhang, Xu; Gang, Daniel Dianchen; Hao, Ji; Chen, Liang; Cooke, Peter; Yan, Hui; Fei, Ling
Abstract : A facile electrospinning strategy to simultaneously and in situ generate Co9 S8 and Ni3 S2 nanoparticles within S-doped carbon nanofiber matrix as free-standing anode materials for LIBs. Abstract : Transition metal sulfides as electrode materials for lithium-ion batteries have attracted significant research attention due to their high theoretical capacity, excellent redox reversibility, and earth abundance. However, this material family still suffers from poor conductivity and experiences huge volume changes. Here, we demonstrate a facile and scalable electrospinning method to prepare Ni3 S2 and Co9 S8 nanoparticles embedded in sulfur doped carbon nanofiber networks as a free-standing anode material for lithium ion batteries. Similar to literature findings, the coupling of two different metal sulfides indeed synergistically promoted the electrochemical performance. Embedding them within individual carbon nanofibers not only enhances the intrinsic conductivity, but also provides a highly stable structure, which results in excellent battery performance. Furthermore, the individual carbon nanofibers intertwine with each other to form a free-standing 3D nanofiber network which acts as a freeway network for fast electron transfer and the pores between fibers allow easy penetration of the electrolyte, namely easy lithium ion access to active nanoparticles. When directly applied as the anode in lithium ion batteries, the free-standing nanofiber mat bypassed all slurry making steps and showed excellent cycling stability with a high specific capacity of 528 mA h g −1 after 200 cycles at a current density of 300 mA g −1 . Good rate capability was also obtained. Additionally, the charge storage process analysis indicated that the pseudocapacitive behavior of the material is attributed to its good performance. This work introduces a facile strategy to simultaneously and in situ generate Co9 S8 and Ni3 S2 nanoparticles within a S-doped carbon fiber matrix via facile electrospinning followed by a one-step heating procedure. It is demonstrated that the free-standing transition bimetallic sulfide nanofibers prepared are very promising for light and small battery applications.